2018
DOI: 10.1016/j.isci.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

SMARCAD1 Phosphorylation and Ubiquitination Are Required for Resection during DNA Double-Strand Break Repair

Abstract: SummaryThe chromatin remodeling factor SMARCAD1, an SWI/SNF ATPase family member, has a role in 5′ end resection at DNA double-strand breaks (DSBs) to produce single-strand DNA (ssDNA), a critical step for subsequent checkpoint and repair factor loading to remove DNA damage. However, the mechanistic details of SMARCAD1 coupling to the DNA damage response and repair pathways remains unknown. Here we report that SMARCAD1 is recruited to DNA DSBs through an ATM-dependent process. Depletion of SMARCAD1 reduces ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 47 publications
5
68
0
Order By: Relevance
“…One possibility is that ATM directly stimulates the resection machinery and/or down-regulates inhibitors of resection. A non-exclusive possibility is that ATM recruits chromatin remodeling activities to DSBs (Chakraborty et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that ATM directly stimulates the resection machinery and/or down-regulates inhibitors of resection. A non-exclusive possibility is that ATM recruits chromatin remodeling activities to DSBs (Chakraborty et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To answer these questions, we employed our previously characterized 293T-based stable cell lines that harbor CRISPR-Cas9-knocked-in homing endonuclease I-SceI target sites into two euchromatic and two heterochromatic regions, in this case, on chromosome 1. As demonstrated in previously, we verified, for each of these four sites, that they a) retained relevant chromatin conformation-specific epigenetic marks, b) that they can each be efficiently cleaved by a transfected cDNA encoding the I-SceI mega-nuclease, and c) chromatin context does not affect repair efficiency (34,35). We used this system first, to evaluate the relative levels of ZEB1 and 53BP1 before and after induction of DSBs.…”
Section: Zeb1 Levels Increase 4-fold At Dsbs In Euchromatin Independmentioning
confidence: 57%
“…Chromosomal aberrations Chromosomal aberrations at metaphase were analyzed as previously described (34,69) EJ-DR-based DSB Repair Pathway Choice Assay I-SceI-mediated DSBs were induced in the EJ-DR cell line as described (40,41). Briefly, at the appropriate time after administration of RNAi and rescue constructs, cells were rinsed 1X in 37˚ PBS, and replenished with complete media (with 10% Tet-minus FCS) containing 1µM Sheild1 (Aobious) and 0.1 µM triamcinolone acteonide (Cayman).…”
Section: Survival Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…2E), two well-established defects observed in ATR-deficient cells. (19) Chromatin immunoprecipitation real-time quantitative PCR analysis found that BRUCE is recruited to DNA damage sites induced by the endonuclease I-SecI in a human fibroblast DR95 cell line, which expresses a pDR-GFP plasmid containing I-SceI cleavage sequence (21) (Fig. 2F).…”
Section: Bruce Accumulates At Dna Damage Sites and Protects Against Rmentioning
confidence: 99%